1967
DOI: 10.1021/bi00863a006
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Role of the Lymphoid System. IV. The Separation of γ-Globulin into Physiologically Active Components by Cellulose Phosphate Chromatography*

Abstract: Chromatography of human 7-globulin on cellulose phosphate columns yielded four distinct fractions, I-IV. The amino acid analyses of the fractions show remarkable similarities though differences do exist.The technique is simple and reproducible. 7-Globulin A (7A) was confined to fraction I and 7globulin M (7M) to fraction II, both as minor com-T A he physiological effect of 7-globulin on autologous blood cells has been demonstrated recently in the dog. It was shown that a specific leucophilic 7-globulin that bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
3

Year Published

1969
1969
2001
2001

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…This is definitely restricted and is expressed by the low rate of phagocytic activity. This rate, as measured in vitro, is at the low Analysis of the patients y-globulin revealed that phosphocellulose frac tion IV [34] is normal in quantity but devoid of activity. It was not pos sible to obtain active extracts following treatment of their ^-globulin with the PMN membrane enzyme leukokinase or with trypsin to release free tuftsin [5][6][7], On the contrary, extracts obtained from such samples were in fact strongly inhibitory to the stimulatory activity of either natural or synthetic tuftsin.…”
Section: Laboratory Findingsmentioning
confidence: 88%
See 2 more Smart Citations
“…This is definitely restricted and is expressed by the low rate of phagocytic activity. This rate, as measured in vitro, is at the low Analysis of the patients y-globulin revealed that phosphocellulose frac tion IV [34] is normal in quantity but devoid of activity. It was not pos sible to obtain active extracts following treatment of their ^-globulin with the PMN membrane enzyme leukokinase or with trypsin to release free tuftsin [5][6][7], On the contrary, extracts obtained from such samples were in fact strongly inhibitory to the stimulatory activity of either natural or synthetic tuftsin.…”
Section: Laboratory Findingsmentioning
confidence: 88%
“…Serum proteins, including --globulin, are normal. Routine frac tionation of y-globulin on cellulose phosphate columns [34] yield normal values. Similarly, yA, yM, and yG,_,, are within normal values [6,7,24], Complement components, C3 and C5, gave normal values along with nor mal biological activity [6,7].…”
Section: Laboratory Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of the natural occurring peptide tuftsin was the culmination of studies by Najjar and coworkers on the physiological role of cytophilic ')I-globulins (1)(2)(3)(4)(5)(6). In that series of communications, it was demonstrated that particular fractions of the immunoglobulins, from mammalian origin, obtained through chromatography on phosphocellulose columns, have selective affinities to different blood cells: the erythrocyte (2, 6), the thrombocyte (6, 7) and the granulocytic leukocyte (I, [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…de yG-globulines standard ou traitées à pH 4 chez un patient hypogammaglobulinémique souffrant d'une anémie hémolytique. Des expériences faites chez le chien et chez l'homme montrent la présence, à la surface des érythrocytes, d'une fraction d'IgG augmentant la viabilité de la cellule [10,27]. Les mêmes auteurs observent qu'une autre fraction d'IgG fixée sur les leucocytes humains, augmente l'acti vité phagocytaire de ces cellules vis-à-vis du staphylocoque doré [10].…”
unclassified